Giant epidermal cyst in the breast requiring reconstruction with the bilobed flap technique — case report - Lopes de Aguiar Araújo, Juliana; Taissa Sampaio Marinho Navarro, Diana; Laise de Menezes Dantas, Macerly; de Sousa Brunet, Gabrielly; dos Santos Lourenço Ferreira, Larissa; Wagner de Sousa, Ubiratan (Mastology, 2025)
Epidermal cysts are one of the most common benign skin lesions, originating in the pilosebaceous unit, and are very common on the scalp, back, and trunk. They usually measure from millimeters to a few centimeters and require surgical treatment only depending on the patient's discomfort. Cases that mimic breast neoplasms are rare. Treatment consists of a minimal incision, with removal of the contents and their capsule, without major complications. We report here the case of a woman with an epidermal cyst in her left breast, which had grown progressively over the years, reaching 6 cm. Because of its size, location, and unfavorable relationship between tumor size and breast size, surgery using an oncoplastic breast remodeling technique was chosen, opting for the use of a bilobed flap to achieve a satisfactory cosmetic result, without loss of breast volume.